Evaluating Student-Built Earthquake Alarm Prototypes: Integrating Engineering Practices Through Real-World Projects in Junior High School - Suminar, Iin; Saputra, M. Reza Dwi; Iqbal, Nur Habib Muhammad (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
Preparing students for 21st-century challenges requires learning experiences that connect scientific knowledge with real-world applications. This study investigates the integration of engineering practices in junior high school physics education through a project in which ninth-grade students designed and built simple earthquake alarm prototypes. The project adopted the PGBU (Pikir, Gambar, Buat, Uji)—a structured design process widely used in Indonesia—to guide students through iterative phases of thinking, sketching, building, and testing. Data from 24 student groups were analyzed using a rubric assessing functionality, application of physics concepts, creativity, construction neatness, and use of recycled materials. Most groups performed at moderate to high levels, with relatively higher performance observed in creativity and functionality. Results also indicated evidence of collaboration and the ability to apply physics concepts in real-world contexts. The project-based implementation of PGBU effectively fostered essential 21st-century competencies such as creative problem-solving, critical thinking, and teamwork. These findings highlight the potential of culturally grounded, design-based learning to support meaningful STEM education in junior high schools.